Circulating Inflammatory Markers Are Inversely Associated with Heart Rate Variability Measures in Type 1 Diabetes. (18th August 2020) - Wegeberg, Anne-Marie L.; Okdahl, Tina; Fløyel, Tina; Brock, Christina; Ejskjaer, Niels; Riahi, Sam; Pociot, Flemming; Størling, Joachim; Brock, Birgitte
Abstract : Introduction . A neuroimmune communication exists, and compelling evidence suggests that diabetic neuropathy and systemic inflammation are linked. Our aims were (1) to investigate biomarkers of the ongoing inflammation processes including cytokines, adhesion molecules, and chemokines and (2) to associate the findings with cardiovascular autonomic neuropathy in type 1 diabetes by measuring heart rate variability and cardiac vagal tone. Materials and Methods . We included 104 adults with type 1 diabetes. Heart rate variability, time domain, and frequency domains were calculated from a 24-hour Holter electrocardiogram, while cardiac vagal tone was determined from a 5-minute electrocardiogram. Cytokines (interleukin- (IL-) 1 α, IL-4, IL-12p70, IL-13, IL-17, and tumor necrosis factor- (TNF-) α ), adhesion molecules (E-selectin, P-selectin, and intercellular adhesion molecule- (ICAM-) 1), and chemokines (chemokine (C-C motif) ligand (CCL)2, CCL3, CCL4, and C-X-C motif chemokine (CXCL)10) were assessed using a Luminex multiplexing technology. Associations between concentrations of inflammatory biomarkers and continuous variables of heart rate variability and cardiac vagal tone were estimated using multivariable linear regression adjusting for age, sex, disease duration, and smoking. Results . Participants with the presence of cardiovascular autonomic neuropathy had higher systemic levels of IL-1 α, IL-4, CCL2, and E-selectin than those without cardiovascular autonomic neuropathy. IL-1 α, IL-4, IL-12, TNF- α, and E-selectin were inversely associated with both sympathetic and parasympathetic heart rate variability measures (p > 0.01 ). Discussion . Our results show that several pro- and anti-inflammatory factors, believed to be involved in the progression of diabetic polyneuropathy, are associated with cardiovascular autonomic neuropathy, suggesting that these factors may also contribute to the pathogenesis of cardiovascular autonomic neuropathy. Our findings emphasize the importance of the neuroimmune regulatory system in the pathogenesis of neuropathy in type 1 diabetes.